Continental margin subsidence from shallow mantle convection: Example from West Africa - Lodhia, Bhavik; Roberts, G.G.; Fraser, A.J.; Fishwick, S.; Goes, S.; Jarvis, J. (2018)
Spatial and temporal evolution of the uppermost convecting mantle plays an important role in determining histories of magmatism, uplift, subsidence, erosion and deposition of sedimentary rock. Tomographic studies and mantle flow models suggest that changes in lithospheric thickness can focus convection and destabilize plates. Geologic observations that constrain the processes responsible for onset and evolution of shallow mantle convection are sparse. We integrate seismic, well, gravity, magmatic and tomographic information to determine the history of Neogene-Recent (<23 Ma) upper mantle convection from the Cape Verde swell to West Africa. Residual ocean-age depths of +2 km and oceanic heat flow anomalies of +16 ± 4 mW m−2 are centered on Cape Verde. Residual depths decrease eastward to zero at the fringe of the Mauritania basin. Backstripped wells and mapped seismic data show that 0.4–0.8 km of water-loaded subsidence occurred in a ∼500 × 500 km region centered on the Mauritania basin during the last 23 Ma. Conversion of shear wave velocities into temperature and simple isostatic calculations indicate that asthenospheric temperatures determine bathymetry from Cape Verde to West Africa. Calculated average excess temperatures beneath Cape Verde are >+100 °C providing ∼103 m of support. Beneath the Mauritania basin average excess temperatures are <−100 °C drawing down the lithosphere by ∼102 to 103 m. Up- and downwelling mantle has generated a bathymetric gradient of ∼1/300 at a wavelength of ∼103 km during the last ∼23 Ma. Our results suggest that asthenospheric flow away from upwelling mantle can generate downwelling beneath continental margins.